2012
DOI: 10.4028/www.scientific.net/amm.166-169.738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Initial Imperfection on the Buckling of Steel Member Wrapped by Carbon Fibre

Abstract: Based on Ježek method of computing the elastic-plastic buckling of the member under the axial compressive load and the bending moment, considering the initial geometric imperfection, the analytical expressions of calculating the ultimate load of buckling about the neutral axis with the maximum moment of inertia for an H-shaped member with flange outsides wrapped by carbon fibre are derived. Using the elastic-plastic finite element method and the theory of nonlinear buckling, the impact of the initial geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These defects have a great influence on mechanical behaviors, causing a decrease in the buckling capacity of tubes under axial loading [3,7]. In addition, many experimental studies have shown that buckling appeared earlier than estimated because of initial imperfections, such as in the case of I-sections [6,8], box sections [3,9,10], equal angle columns [11][12][13], T-sections [14], circular sections [15,16], and C-sections [17][18][19] for steel structures or concrete structures [20][21][22], composite structures [23][24][25], and alloy structures [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These defects have a great influence on mechanical behaviors, causing a decrease in the buckling capacity of tubes under axial loading [3,7]. In addition, many experimental studies have shown that buckling appeared earlier than estimated because of initial imperfections, such as in the case of I-sections [6,8], box sections [3,9,10], equal angle columns [11][12][13], T-sections [14], circular sections [15,16], and C-sections [17][18][19] for steel structures or concrete structures [20][21][22], composite structures [23][24][25], and alloy structures [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, analytical solutions often demonstrate a limitation as the structures are simplified with regular geometry. In the case of more complex structures, the numerical finite element technique has been widely applied to investigate the influence of initial imperfections on the buckling behavior of compression members, such as sigma section members [17], I-section steel columns wrapped by carbon fibers [24], cylindrical pipes made by carbon fiber-reinforced plastic material [23], braced columns [33], and multi-layer beams [25]. However, finite element analysis of buckling problems is mainly based on commercial software, for instance, ANSYS [7,19], ABAQUS [23,27], and NASTRAN [17].…”
Section: Introductionmentioning
confidence: 99%